Collaborative transportation planning distinguishing old and new shippers for small-medium enterprise. (3rd April 2018) - He, Pengfei; Li, Jing; Jiang, Yiping; Wang, Xin
Abstract: This paper conducted a research on the vehicle routing problem (VRP) for small–medium enterprise (SMEs) considering new and old shippers. The problem is motivated by a real-world scenario found between Changzhou's small or medium enterprises (Shippers) and transportation companies (Carriers). Since the service time is different for new and old shippers in the real world, we obtained a set of rich VRP considering time windows and the working time of the vehicle, as well as distinguishing between old and new shippers. We also propose a hybrid algorithm that consists of ant colony optimization (ACO) and tabu search (TS). Carrier's trade-off point of orders' number is calculated by the hybrid algorithm. Meanwhile, scenarios of deterministic versus stochastic shippers' demand and collaborative versus non-collaborative carriers are optimized by the algorithm. The results show that the collaborative transportation planning could improve the profits of carriers.